THE IDEAS OF RECHTERLIJK PARDON AS A RESTORATIVE JUSTICE APPROACH: FROM VENGEANCE TO RECOVERY? - Abdurrakhman Alhakim (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
After the rebirth of the discourse on ratifying the Draft Criminal Code (RKUHP) on September 24, 2019, which will be confirmed in the plenary session of the House of Representatives of the Republic of Indonesia (DPR RI), however, the emergence of this information to the surface related to the ratification of the RKUHP gave a negative response by the community, especially for activists and students. It is because some of the contents of the RKUHP are considered controversial and have multiple interpretations, which are feared to create legal uncertainty in Indonesia. Sentencing through imprisonment for anyone who violates has implications and a domino effect (domino effect) related to the phenomenon of over-capacity in Correctional Institutions. One solution to overcome this is to apply rechterlijk pardon through a restorative justice approach. This research is descriptive with the type of juridical-normative research. The type of approach used is the statutory approach and the conceptual approach. The results can provide the reform of the criminal law system, which initially focused on retributive to focus on the goal of restitution. Therefore, there is an urgency to ratify the RKUHP, which has the idea of rechterlijk pardon to change the paradigm from retaliation to recovery, as a manifestation of the restorative justice approach in Indonesia.